Late Hallstatt and Early La Tène gold and silver beads in southeast Pannonia - Potrebica, Hrvoje (Array, 2014)
Beads made of silver and gold appear in the territory of southern Pannonia in the period between 6th and 4th cent. BC in rich female burials. They could have been made in local workshops, although influences from the south Hellenistic centres are also present.